Perancangan Interior Science Center untuk Anak Berusia 3 sampai 12 Tahun di Surabaya - Olivia Higiantoro; Cok Gede Padmanaba; Sherly de Yong (Intra, 2016)
Interior design of Science Center for children aged 3 to 12 years in Surabaya is designed to support learning process in formal school, seeing the lack of children’s interest in learning because of the unattractive way of learning. Science Center is there to provide an innovative learning facilities with interactive media for children. The design method process is starting from finding out what children need in the science center, then entered the design process, and the last stage is to add small details needed, and each process will be analyzed and evaluated to get the maximal result. In accordance with the concept of “Brain New World”, children is invited to enter the new learning world that is more interesting with various areas and interactive furniture, like touch screen furniture and hologram.